Analysis of Understanding Concepts and Misconceptions in Physics Learning: SLR (Systematic Literature Review) - Sukmawati, Sukmawati; Wati, Mustika; Dewantara, Dewi; Setiono, Isnaini Agus (Jurnal Pembelajaran Fisika, 2024)
An educator often faces the challenge of ensuring that students truly understand the concepts taught or not, especially in physics learning. As one of the branches of science, physics aims for students to be competent in mastering the principles and concepts of physics. Misunderstanding of concepts will certainly hinder learning objectives so concrete steps are needed to overcome misconceptions. If misconceptions can be overcome, this will have a positive impact on students' conceptual understanding. This study aims to analyze conceptual understanding and misconceptions in physics learning. The method used is the Systematic Literature Review (SLR) through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) procedure. This study analyzed 24 national articles accredited by sinta 1, sinta 2, and scopus that discussed students' conceptual understanding and misconceptions in physics learning. The results showed that using innovative learning models such as the Learning Cycle (LC) 7E, generative learning, and guided inquiry significantly improved students' conceptual understanding. In addition, the development of modules based on Science, Environment, Technology, and Society (SETS) and the use of technology such as E-LKPD based on the Physics Toolbox Sensor Suite proved effective in strengthening the understanding of physics concepts. On the other hand, misconceptions are still widely found in the basic concepts of physics, which are identified through the Three-Tier Test and Four-Tier Diagnostic Test. Therefore, the selection of the right learning model and the use of technology in teaching are key factors to reduce misconceptions and improve students' understanding of physics.Keywords: Misconceptions, physics learning, tiered diagnostic tests, understanding concepts. DOI: http://dx.doi.org/10.23960/jpf.v12.n2.202403